Peran Penting Komunikasi Internasional Dalam Hubungan Masyarakat - Lintang Wahyu Charisa Raharjo; Chontina Siahaan (CV. ITTC INDONESIA, 2021)
International communication has a focus on the study of international relations, which interacts between countries and their governments through diplomacy. In international public relations, communication science based on IR is the foundation. The research method uses quantitative techniques to collect data numerically. The results of the study stated that communication in international public relations is important. Global languages help in establishing bilateral and multilateral public relations. The application of international communication in global public relations is an effective thing.